KOMODIFIKASI, DISABILITAS DAN TELEVISI - Bonardo Marulitua A (Universitas Kristen Satya Wacana, 2016)
In Indonesia the presence of the mass media especially television has become animportant part in the life of the community. As agents of capitalism, television has beenproducing events capable of